Teacher’s Metacognitive Strategies Applied in Teaching English for Non-Formal Learning Community - Meiristiani, Noeris; Nisrina Nurkhanifah; Yuvita, Yuvita (Jurnal Bahasa Inggris, 2020)
This paper examined the teacher’s metacognitive strategies application in teaching English at non-formal learning community. It is a descriptive qualitative research. It focused on activities in the learning community, which the researchers analyzed the teacher’s metacognitive strategies. The instruments used were interview and questionnaire. In this study, the roles of the researchers were as an investigator and interviewer. The subjects of this research are one English teacher and ten students at PKBM Cahya Mulya Taman Pemalang. The study revealed that eventhough the teacher could structurally apply the aspects of metacognitive strategies, he found some difficulties in applying some aspects due to the limited amount of the teaching time allocation, the students’ lack of English vocabulary mastery, and limited teaching facilities. Some efforts were done to overcome the problems.